Lateral Hypothalamic Control of the Ventral Tegmental Area: Reward Evaluation and the Driving of Motivated Behavior - Tyree, Susan M.; de Lecea, Luis (Frontiers in Systems Neuroscience, 2017)
The lateral hypothalamus plays an important role in many motivated behaviors, sleep-wake states, food intake, drug-seeking, energy balance, etc. It is also home to a heterogeneous population of neurons that express and co-express multiple neuropeptides including hypocretin, melanin-concentrating hormone, cocaine- and amphetamine- regulated transcript, and neurotensin. These neurons project widely throughout the brain to areas such as the locus coeruleus, the bed nucleus of the stria terminalis, the amygdala, and the ventral tegmental area. Lateral hypothalamic projections to the ventral tegmental area are believed to be important for driving behavior due to the involvement of dopaminergic reward circuitry. The purpose of this article is to review current knowledge regarding the lateral hypothalamic connections to the ventral tegmental area and the role they play in driving these behaviors.